STATISTICAL PROCESS CONTROL SEBAGAI ALAT PENGAWASAN HARGA POKOK PENJUALAN CRUDE PALM OIL PERUSAHAAN PERKEBUNAN KELAPA SAWIT - Shofwan Andri; Tri Kartika Yudha (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2018)
Statistical Process Control (SPC) is the use of statistical methods to improve a production process in measuring production performance so that the process remains statistically controlled. This Statistic is based on the understanding that will never the same production and production costs obtained each year, then the automatic acquisition cost of goods sold will never be the same. Therefore, in this research will focus the Statistical Process Control on the cost of goods sold supervision process which during this time management may not be able to directly supervise the use of cost until the determination of the cost of goods sold. Moreover, the existence of Statistical Process Control will assist management in overseeing the price stable CPO sales stakes and are in statistical control. This research was conducted at PT. Sumber Sawit Makmur which is a private plantation company oriented to the field of oil palm plantation equipped with its management plant. The purpose of this study is to (1) analyze and evaluate how the implementation of Statistical Process Control acts as a supervisory tool on CPO selling price, (2) reexamination of cost of goods sold outside statistical control, (3) to know how to apply Statistical Process Control at the Oil Palm Plantation Company. This research was conducted at Palm Oil Company in Medan City. The method of analyst technique was done by using descriptive method by using Statistical Process Control. Data obtained and collected will be analyzed using Statistical Process Control Methods on Individual X and MR control charts. The results of research showed that the use of statistical control process at PT. Sumber Sawit Makmur to assess behavior on CPO cost of goods sold. The control limits that have been determined on the control chart X are: CL = 5.857, UCL=7.845, LCL= 3.869 and on the MR control chart that is CL=747, UCL=2.441, LCL=0. On the control chart X, CPO/Kg cost of goods sold at PT. Sumber Sawit Makmur is not in statistical control since from the 10 years data there are 3 years not in statistical control. Those are in 2005, 2006, and 2014. CPO/Kg cost of goods sold is not in statistical control on account of special causes namely CPO/Kg production and cost of production. Meanwhile on the MR control chart, the CPO/Kg cost of goods sold is in statistical control.